Micropatterning in bistable cholesteric device with Bragg's reflection - Gritsenko, M.I.; Kucheev, S.I.; Lytvyn, P.M.; Tishenko, V.G.; Tkach, V.M.; Yelshansky, V.B. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2006)
In this work, the method to form bistable patterning in a cholesteric cell with Bragg’s reflection in the visible spectral range is demonstrated. In order to reach this, we used a Si/SiO₂ structure in which a potential relief on SiO₂ surface is induced due to enrichment and depletion of required form areas of the silicon near-surface layer during external electric field action. The patterning of enrichment is determined by the positive charge embedded into SiO₂ film, which is formed by thermodiffusion of aluminum atoms.